Real‐world outcomes for 205 patients with chronic lymphocytic leukemia treated with ibrutinib. (26th August 2020) - Aarup, Kathrine; Rotbain, Emelie Curovic; Enggaard, Lisbeth; Pedersen, Robert Schou; Bergmann, Olav Jonas; Thomsen, Rasmus Heje; Frederiksen, Mikael; Frederiksen, Henrik; Nielsen, Tine; Christiansen, Ilse; Andersen, Michael Asger; Niemann, Carsten Utoft
Abstract: Ibrutinib has now been approved for treatment of chronic lymphocytic leukemia (CLL) in both front‐line setting and as later‐line treatment. However, knowledge about the outcomes and adverse events (AE) among patients at a population‐based level is still limited. Objectives: To report outcomes and AEs in a population‐based cohort treated with ibrutinib outside clinical trials. Methods: We conducted a multicenter, retrospective cohort study including all patients with CLL treated with ibrutinib. Results: In total, 205 patients were included of whom 39 (19%) were treatment‐naïve. The median follow‐up was 21.4 months (interquartile range (IQR), 11.9, 32.8), the estimated overall survival at 12 months was 88.8% (95% confidence interval (CI); 84.3%, 93.3%), and the estimated progression‐free survival at 12 months was 86.3% (95% CI; 81.3%, 91.2%). During follow‐up, 200 (97.6%) patients had at least one AE and 100 (48.8%) patients had at least one grade ≥3 AE. Eighty‐six patients (42.0%) discontinued ibrutinib, hereof 47 (54.7%) due to AEs and 19 (22.1%) had progression of CLL or Richter transformation. Conclusions: In our study, we find comparable, though slightly inferior, overall, and progression‐free survival, and discontinuation due to toxicity was higher compared with clinical trials. Patient training and information may improve treatment adherence outside clinical trials.